Hierarchical Fabrication of Engineered Vascularized Bone Biphasic Constructs via Dual 3D Bioprinting: Integrating Regional Bioactive Factors into Architectural Design - Cui, Haitao; Zhu, Wei; Nowicki, Margaret; Zhou, Xuan; Khademhosseini, Ali; Zhang, Lijie Grace (Advanced healthcare materials, 2016)
A biphasic artificial vascularized bone construct with regional bioactive factors is presented using dual 3D bioprinting platform technique, thereby forming a large functional bone grafts with organized vascular networks. Biocompatible mussel‐inspired chemistry and “thiol‐ene” click reaction are used to regionally immobilize bioactive factors during construct fabrication for modulating or improving cellular events.